Baicalein Alleviates Neuropathic Pain by Inhibiting Microglial Activation and Inflammation Via the TLR4/NF-κB p65 Pathway - Cai, Jieyi; Luo, Ling; Yuan, Min; Li, Hui; Chen, Lü; Peng, Qianqian; Zhu, Changlai; Gu, Yun (Planta Medica, 2025)
Clinically, there is a significant unmet need for effective treatments for chronic neuropathic pain. Commonly used drugs, such as opioids, are primarily designed for acute pain management and are associated with substantial adverse effects, including tolerance and addiction. Therefore, the development of safe and effective therapies is of paramount importance. Baicalein (BA), a flavonoid compound extracted from Scutellaria baicalensis, has anti-inflammatory, antibacterial, and anti-proliferative activities against tumor cells and has been used to treat various acute and chronic conditions without notable side effects. In this study, we employed the spared nerve injury (SNI) pain model to investigate the therapeutic efficacy of BA on neuropathic pain and its underlying mechanisms. Results showed that BA effectively alleviated SNI-induced hyperalgesia and the progression of chronic pain in a dose-dependent manner by inhibiting glial cell activation, immune cell infiltration, and inflammatory responses. Additionally, using an in vitro microglial inflammation model, we further confirmed that BA inhibits M1 polarization of microglia and the expression of pro-inflammatory factors by modulating the TLR4/NF-κB p65 signaling pathway. Our results suggest that BA holds promise as a potential therapeutic agent for treating neuropathic pain caused by nerve injury or diseases.
Keywords: Scutellaria baicalensis; Lamiaceae; baicalin; neuropathic pain; glial cell activation; inflammation; TLR4/NF-κB